Impact of Board Diversity and Institutional Ownership on Performance and Risk of LQ45 Firms - Syarila Asri Febiani; Naelati Tubastuvi; Wida Purwidianti; Restu Frida Utami (MAKSIMUM: Media Akuntansi Universitas Muhammadiyah Semarang, 2026)
This study examines the influence of board diversity (gender, nationality, and age) and institutional ownership on company performance and risk among companies listed on the LQ45 index from 2020 to 2023. This study employs a quantitative approach, utilising secondary data collected from company annual reports. The sample comprises 25 companies and 100 observations spanning 4 years. The analysis was conducted using multiple linear regression in StataMP 17 to determine the influence of independent variables on company performance, measured by Return on Assets (ROA), and on company risk, calculated using the Debt-to-Equity Ratio (DER). The results indicate that board diversity has a significant positive effect on ROA, while gender and age diversity do not show a substantial impact on company performance. On the other hand, institutional ownership has a significant adverse effect on ROA, indicating that higher institutional ownership tends to reduce a company's performance. All independent variables also had no significant impact on company risk (DER). These findings suggest that, although board diversity and institutional ownership can theoretically enhance oversight and decision-making, their practical implications remain limited due to the low proportion of female, foreign, and young directors, as well as the lack of active institutional involvement. This study contributes to the corporate governance literature in the Indonesian capital market and suggests that future research should include mediation or moderation variables to gain a more comprehensive understanding.